Gamified Eco Hero Academy for Elementary Environmental Education: Akademi Pahlawan Lingkungan Berbasis Permainan untuk Pendidikan Lingkungan Tingkat Dasar (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Environmental education in elementary schools plays a crucial role in shaping students’ ecological awareness and character development amid escalating global environmental challenges. Specific Background: In Indonesia, a significant gap persists between theoretical instruction on environmental conservation and students’ daily practices, particularly in waste management. Knowledge Gap: Conventional teaching methods remain largely lecture-based and less responsive to digital-native learners, resulting in limited engagement and weak integration of knowledge and action. Aims: This study presents the development of “Eco-Hero Academy,” a gamification-based digital learning application designed to integrate environmental knowledge, attitudes, and practical skills for elementary students. Results: The application integrates structured menus comprising competency assessment (affective, cognitive, psychomotor domains), interactive materials in slide and video formats covering six core environmental topics, and six educational game variations including word guessing, rapid quizzes, secret missions, storytelling, clean relay, and clean–dirty categorization. Novelty: The platform systematically combines gamified challenges, point accumulation, ranking systems, and multimedia content within a single integrated learning ecosystem tailored to elementary learners. Implications: Eco-Hero Academy offers a structured digital instructional medium that bridges theory and practice, supports teachers’ instructional strategies, and promotes sustained ecological awareness through interactive and personalized learning experiences. Keywords: Gamification, Environmental Education, Elementary School, Instructional Media, Waste Management Key Findings Highlights: The platform integrates competency assessment with multimedia environmental content and structured challenges. Six interactive game formats facilitate direct application of ecological knowledge in simulated contexts. The system combines ranking, scoring, and personalized profiles within a unified digital learning environment.